Red harvester ants Pogonomyrmex barbatus (Smith, 1858) (Hymenoptera: Formicidae) do not distinguish between sorghum head mold symptomatic and asymptomatic seeds - Elliott-Vidaurri, Lilly V.; Penn, Hannah J.; Choudhury, Robin A. (Entomological Communications, 2024)
Red harvester ants, Pogonomyrmex barbatus (Smith, 1858) (Hymenoptera: Formicidae), common in the Lower Rio Grande Valley of Texas, are known to gather seeds from areas around their nests and store the seeds inside their nests for later consumption. As these ants often nest in and near agricultural fields, some of these seeds may be from crops and may also be infected with fungal plant pathogens. These pathogens can degrade seed coats and may cause the seeds to rot within the ant nests, decreasing storage time and potentially spreading the pathogen to other stored seeds. We studied how head mold, a common sorghum disease, changed ant preferences for sorghum seeds. Using seed depots, we evaluated foraging preferences for sorghum seeds with and without head mold and then monitored how many seeds of each type were collected by the colonies after 1, 2, 4, and 24 hours. We found that red harvester ants did not have any significant preference for infected or uninfected seeds, taking both equally over time. Given this non-preference, ants were assumed to be storing infected seeds next to uninfected seeds within their colonies. However, the risk that stored pathogen-infected seeds poses as a source of future seed infection to seeds within the nest and plants in the surrounding field needs to be further examined.